Tubular cell and keratinocyte single-cell transcriptomics applied to lupus nephritis reveal type I IFN and fibrosis relevant pathways - Der, Evan; Suryawanshi, Hemant; Morozov, Pavel; Kustagi, Manjunath; Goilav, Beatrice; Ranabothu, Saritha; Izmirly, Peter; Clancy, Robert; Belmont, H. Michael; Koenigsberg, Mordecai; Mokrzycki, Michele; Rominieki, Helen; et al. (Nature immunology, 2019)
The molecular and cellular processes that lead to renal damage and to the heterogeneity of lupus nephritis (LN) are not well understood. We applied single-cell RNA sequencing (scRNA-seq) to renal biopsies from patients with LN and evaluated skin biopsies as a potential source of diagnostic and prognostic markers of renal disease. Type I interferon (IFN)-response signatures in tubular cells and keratinocytes distinguished patients with LN from healthy control subjects. Moreover, a high IFN-response signature and fibrotic signature in tubular cells were each associated with failure to respond to treatment. Analysis of tubular cells from patients with proliferative, membranous and mixed LN indicated pathways relevant to inflammation and fibrosis, which offer insight into their histologic differences. In summary, we applied scRNA-seq to LN to deconstruct its heterogeneity and identify novel targets for personalized approaches to therapy. Nephritis is a major cause of lupus morbidity. Putterman and colleagues use single-cell RNA sequencing on human renal and skin biopsies to describe the expression landscape associated with lupus nephritis.